Peningkatan Produksi Biogas dari Palm Oil Mill Effluent (POME) dengan Fluidisasi Media Zeolit Termodifikasi pada Sistem Batch - Firda Mahira Alfiata Chusna; Melly Mellyanawaty; Estin Nofiyanti (Jurnal Rekayasa Proses, 2020)
The production of crude palm oil (CPO) in Indonesia tends to increase over time. Palm oil mill effluent (POME) is the wastewater generated from the palm oil mill process with high organic content. POME is a potential source for anaerobic digestion due to its high organic content. The challenge of POME treatment using an anaerobic process is to enhance biogas production with high soluble chemical oxygen demand (sCOD) removal efficiency. The purpose of this study was to evaluate the effect of selected trace elements addition onto zeolite as immobilization media to the anaerobic digestion of POME in a fluidized batch system. Natural zeolite was used as the medium to immobilize microorganisms in an anaerobic fluidized bed reactor (AFBR). This study used three trace elements impregnated to natural zeolites, i.e. Ni2+, Zn2+, Mg2+. The result shows that Ni2+ and Zn2+ improve the methanogenesis process, prevent the accumulation of VFA as an intermediate product and increase the methane (biogas) production. Meanwhile, Mg2+ only reduced sCOD significantly but it did not affect methane production. Fluidization enhanced the performance of the POME anaerobic digestion process. The fluidization provide a positive effect to enhance biogas production and sCOD removal. The efficiency of sCOD removal in the entire reactors were 80.82%; 81.77%; 75.89% for AFBR-Ni; AFBR-Zn and AFBR-control respectively. The total volume of methane produced by the three AFBR were 163,04; 136,42; 62,79 (in ml CH4 / g sCOD) for AFBR-Ni; AFBR-Zn and AFBR-control, respectively. A B S T R A KProduksi crude palm oil (CPO) di Indonesia cenderung meningkat seiring bertambahnya waktu. Palm oil mill effluent (POME) adalah air limbah yang dihasilkan dari proses penggilingan kelapa sawit dengan kandungan organik yang tinggi. Tantangan dalam mengolah POME menggunakan proses peruraian anaerobik adalah untuk meningkatkan produksi biogas dengan efisiensi penurunan soluble chemical oxygen demand (sCOD) yang tinggi. Tujuan dari penelitian ini adalah mengevaluasi pengaruh penambahan trace element terseleksi pada media imobilisasi zeolit terhadap proses peruraian anaerobik limbah POME dengan sistem batch terfluidisasi. Zeolit alam berperan sebagai media imobilisasi mikroorganisme dalam anaerobic fluidized bed reactor (AFBR). Penelitian ini menggunakan tiga trace element yang diimpregnasikan pada zeolit alam yaitu Ni2+, Zn2+, Mg2+. Hasil penelitian menunjukkan bahwa Ni2+ dan Zn2+ sebagai trace element dapat meningkatkan proses metanogenesis dan mencegah akumulasi VFA sebagai produk antara serta meningkatkan produksi gas metana (biogas). Mg2+ sebagai trace element menurunkan sCOD dengan cukup signifikan namun tidak diimbangi dengan banyaknya metana yang dihasilkan. Fluidisasi meningkatkan performa dari proses peruraian anaerobik POME. Proses fluidisasi memberi pengaruh positif dalam meningkatkan produksi biogas dan soluble chemical oxygen demand (sCOD) removal. Nilai sCOD removal yaitu 80,82%; 81,77%; 75,89% berturut-turut untuk AFBR-Ni; AFBR-Zn dan AFBR-kontrol. Total volume metana yang dihasilkan oleh ketiga AFBR yaitu 163,04; 136,42; 62,79 (dalam ml CH4 / g sCOD) berturut-turut untuk AFBR-Ni; AFBR-Zn dan AFBR-kontrol.